2021
DOI: 10.1021/acs.cgd.1c00428
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of the Thermally and Stress-Activated Glide of a ⟨0001⟩{11̅00} Screw Dislocation in AlN

Abstract: The low-temperature plasticity of aluminum nitride (AlN) is determined by the interaction between edge and screw dislocations. However, the motion of screw dislocations and their glide mechanisms have not been evaluated. In this study, the motion of a ⟨0001⟩{11̅ 00} screw dislocation in a single crystal of AlN is explored by molecular dynamics simulations using LAMMPS software with the Stillinger−Weber (SW) potential. Four modes of thermally activated motion are observed under different conditions of temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…10 Experimental studies have shown that most threading dislocations are perfect edge dislocations. 11,12 They have Burgers vector b = a/3⟨112̅ 0⟩ and slip on the {0001}, {101̅ 0}, and {101̅ 1} planes. They are labeled as basal dislocations, prismatic dislocations, and pyramidal dislocations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Experimental studies have shown that most threading dislocations are perfect edge dislocations. 11,12 They have Burgers vector b = a/3⟨112̅ 0⟩ and slip on the {0001}, {101̅ 0}, and {101̅ 1} planes. They are labeled as basal dislocations, prismatic dislocations, and pyramidal dislocations.…”
Section: Introductionmentioning
confidence: 99%
“…The AlN crystal structure is a well-known wurtzite-type structure with lattice parameters of a = 0.311 nm, c = 0.498 nm, and c / a = 1.6 . Experimental studies have shown that most threading dislocations are perfect edge dislocations. , They have Burgers vector b = a /3⟨112̅0⟩ and slip on the {0001}, {101̅0}, and {101̅1} planes. They are labeled as basal dislocations, prismatic dislocations, and pyramidal dislocations.…”
Section: Introductionmentioning
confidence: 99%